Analisis Dampak Pasca Pemekaran Daerah di Provinsi Papua Barat Daya - Aditya Wahyu Saputra; Shahibunnahar Shahibunnahar; Putri Febriyanti; Nur Aida Irsyada; Omi Omi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Regional expansion is a local political action by expanding or reducing subdivisions of regional areas, whether new provinces, districts/cities, to improve public services and community welfare. The object used as focus in this research is Southwest Papua Province. The purpose of this writing is to analyze the impact of post-regional expansion in Southwest Papua Province. The method used in this research is a qualitative research technique with a literature study approach. The research results show that regional expansion in Southwest Papua Province has implications for community welfare, employment, human development and the economy.